Yellow fluorescent graphene quantum dots as a phosphor for white tunable light-emitting diodes. Issue 16 (21st March 2019) - Yin, Luqiao; Zhou, Jipeng; Li, Weitao; Zhang, Jianhua; Wang, Liang
Abstract : Tunable color temperature of graphene quantum dot-based white lighting emitting diodes had been achieved adjusting the thickness and concentration of color convert matrix. Abstract : In recent decades, quantum dots have been considered to be highly promising photoluminescent materials for white light devices. During the application of quantum dots in the fabrication of white LEDs, the spectrum and color temperature of the devices are modulated; these devices often involve quantum dots with different emission wavelengths. In this study, yellow-green emitting graphene quantum dots (GQDs) were fabricated using a simple, low-cost and eco-friendly method. The obtained GQDs were cast in UV-curable siloxane. Then, a polymer film with superior optical transparency and excellent monodisperse properties of GQDs was formed. Via the simple adjustment of thickness and the GQD concentration of the color convert matrix, tunable color temperatures (3196–10 870 K) of the GQD-based white light-emitting diodes (LEDs) were achieved. The CIE (Commission Internationale de L'Eclairage) coordinates of the GQD-based white light-emitting diodes matched well with the blackbody radiation curve. Using the fluorescent polymeric matrix in white LEDs, good quality emission and gratifying stability could be obtained. Moreover, this indicates that this technology has the potential for applications in high-end lighting.